Simulational sensation with C++ - Kumar, Vivek (Alpha Science International, 2011)
Simulational Sensation with C++ mainly emphasises on two goals. First, teaching how to display the inner happenings of a process or a program logic, called 'simulation'. Secondly, how to program using OOPs i.e. the proper way of programming in Object Oriented Languages, especially C++. This book contains a variety of standard programming problems from various fields of computer science like data structures, operating systems, graphics, numerical methods etc and demonstrates these problems in a step by step sequence. It starts every problem from defining the problem, discussing the core logic to solve the problem, a formal algorithm, source code of the problem and finally, the screen outputs.